Dampak Riba mendatangkan Kebinasaan: Sebuah Tinjaun Hadis - Fauziah, Weni Luthfiani (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss the hadith about the prohibition of usury. This research method uses a qualitative type through literature study with content analysis. The results and discussion of this study include general views on usury, hadith about usury, and prohibitions and threats of usury behavior in the perspective of hadith. This study concludes that usury in the hadith is prohibited and forbidden by Allah and His Messenger and is included in the case that can destroy.